2013
DOI: 10.2478/jrp-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

The concentration quenching of photoluminescence in Eu3+-doped La2O3

Abstract: This work explores the influence of dopant concentration on photoluminescent emission and kinetics of Eu 3+ -doped (0.2−10 at.%) nanocrystalline lanthanumoxide powders. The X-ray diffraction analysis confirmed that all samples crystallize in La 2 O 3 hexagonal phase with space group P3m1. Transmission electron microscopy showed particles with non-uniform shape and diverse size distribution with an average particle size of (95 ± 5) nm. The room temperature photoluminescence spectra of all samples contain charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…The integral intensity was the highest for the sample doped with 2% Eu2O3 (Figure 2b). Above that concentration, the quenching mechanism caused the intensity to decrease [34]. The Raman, IR and absorption spectra were aimed to investigate whether the doping with Eu 3+ , Tb 3+ or both has an impact on the structural properties of the studied GTS glasses.…”
Section: Resultsmentioning
confidence: 99%
“…The integral intensity was the highest for the sample doped with 2% Eu2O3 (Figure 2b). Above that concentration, the quenching mechanism caused the intensity to decrease [34]. The Raman, IR and absorption spectra were aimed to investigate whether the doping with Eu 3+ , Tb 3+ or both has an impact on the structural properties of the studied GTS glasses.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the luminescent center concentration should be accompanied by an increase in the intensity of emitted light due to higher absorption efficiency [ 33 ]. In Figure 8 , it can be observed that the aerogel with 50% mol of Eu 3+ has the highest luminescence intensity.…”
Section: Resultsmentioning
confidence: 99%
“…Since the La2O3:Eu 3+ aerogels have a strong emission only at 793 nm, we can assume that the Eu ions might be situated at a symmetrical site. An increase in the luminescent center concentration should be accompanied by an increase in the intensity of emitted light due to higher absorption efficiency [33]. In Figure 8, it can be observed that the aerogel with 50% mol of Eu 3+ has the highest luminescence intensity.…”
Section: Photoluminescent Propertiesmentioning
confidence: 97%
See 1 more Smart Citation

A New Ultrafine Luminescent La2O3:Eu3+ Aerogel

García Ramírez,
García Murillo,
Carrillo Romo
et al. 2023
Gels
“…En dichos estudios, se observa que el fenómeno de desactivación o apagamiento de la emisión, relacionada con la concentración del dopante, generalmente ocurre entre el 3 y el 12%. Sin embargo, los valores registrados con mayor frecuencia oscilan entre el 5 y 7% razón por la cual se eligió el valor promedio, 6% [95][96][97][98][99][100][101][102].…”
Section: Los Precursores Inorgánicosunclassified